Keeping vigil over the profession: a grounded theory of the context of nurse anaesthesia practice - MacDonald Marjorie A; Schreiber Rita S (BMC, 2010)
Abstract Background Nurse anaesthetists in the US have faced continued, repeated challenges to their profession. Regardless, they have met these challenges and have established themselves as major anaesthesia care providers. In this paper we address the research question: How do certified registered nurse anaesthetists (CRNAs) manage the socio-political context in which they provide care for their patients? Methods Grounded theory was used to explore how nurse anaesthetists protect and promote their profession. Purposive, snowball, and theoretical sampling was used and data were collected through participant observation and interviews conducted at a conference of the professional association, an educational program, by telephone, email exchanges, and time spent in operating rooms and an outpatient surgical clinic. Analysis included coding at increasingly abstract levels and constant comparison. Results The basic social process identified was Keeping Vigil Over the Profession, which explains how nurse anaesthetists protect and promote their profession. It is comprised of three contextual categories: Establishing Public Credibility through regulatory and educational standards, Political Vigilance and taking action in governmental and policy arenas, and Tending the Flock through a continuous information loop between local and administrative/political levels. Conclusions From our study of the context of nurse anaesthesia practice, it is clear that CRNAs are dedicated to protecting their ability to provide high quality patient care by maintaining constant vigilance over their profession.